The Active Role of Art Therapy in the Patient Community and the Effect of This Component on the External Body and Internal Spaces in Medical Centers - Sania Sami (Current Approaches in Science and Technology Research Vol. 1, 2021)
The use of art for healing is not a new phenomenon and the history of human life has been familiar with the subject of art in healing for thousands of years. "Artistic elements in the form of paintings and drama have been used in the first civilizations for several centuries BC to reduce fear and anxiety, to create power and strength, and to convey information. "Aristotle and other philosophers have used poetry and drama for the health and purification of the soul. To this day, painting, drama, and music are used in creative art therapy to rehabilitate all diseases and for all ages from childhood to old age. Accordingly, the impact of art on human life has been studied from an architectural point of view in the design of medical centers. Some of the human concerns in the realm of healthcare have always been the strict, cold, and lifeless forms of health centres, as well as the lack of accessibility to them. With the admission to these institutions and the escalation of stressors induced by disease and therapy, the mental state of patients has increasingly gained more attention. Medication, which has been a necessary part of human life since ancient times, is classified into two categories: Physical and mental. Persons' physical improvement was influenced by the first dimension, while individuals' readiness to cope with the treatment process was influenced by the second dimension. Every medical facility was made up of distinct but interconnected units that combined to form the two components. With the rising relevance of this issue, the shape of these buildings and their access were the key problems discussed in these centres, so that they could complete treatment by conducting patients in a simple and quick manner, in a more comfortable setting, with the least amount of time spent, and away from any type of environmental stress imposing in this complex. Finally, different investigations and scientific advances have revealed that the more environmental pressures are reduced in physical and mental dimensions, and the more the psychological dimensions of patients are analysed, the improvement of patients would be faster. This study has also investigated these components in the interaction with art and art therapy and their impacts on each other. Physical studies, data gathering, and data interpretation and analysis were all regarded initial principles in this study. This study is a qualitative-quantitative study in which the field technique and content analysis were utilised in two sections, with qualitative studies and survey study in the qualitative studies and analysis portion. In this area, all written and oral references are studied and collected, and their contents are utilised to extract the principles, the basis, and the best solutions for designing an effective medical and health centre that meets the treatment and psychological needs of patients, as well as the application of art features.